Frank's frock: book 6 - Lyes, Lucy; Crossley, Dick (London, Ladybird, 2000)
To support the phonic work that all 4 to 7 year olds do at school, Ladybird has developed a phonic reading scheme. Part of that scheme, this story helps children have fun learning the relationship between letters and sounds.